If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = 4 + ln(x + -1) Reorder the terms: y = 4 + ln(-1 + x) y = 4 + (-1 * ln + x * ln) y = 4 + (-1ln + lnx) Solving y = 4 + -1ln + lnx Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = 4 + -1ln + lnx
| 5(a-4)=3a+14 | | 2(5x-3)-2x+7= | | -5(3t-2)+7t=4t-9 | | 3x-7+6x+2= | | -5(3t-2)+4t=8t-6 | | -14+n=-11 | | 2X^2+19x+80=0 | | 54=-3/4p | | 9x+y=-26 | | f(0)=(2x^(2)-10)/(7x-5) | | 1.21x=3.2 | | 3.2x=1.21 | | X+-11=-12 | | -2(a+3)-5=-4(a-2)+1 | | 3(7m+4)+5=6(5m-3)-4m | | -21+8+3x= | | 5(2c+4)+4c=8(3c-2)+6 | | -1=3t-19 | | 7=w-(-7) | | 4(x+1)+2x=3(x+5)+1 | | 4+5a=-16 | | 4a-2c/2 | | 2(3a+5)+4=3(3a+2)-a | | 3(4m+5)+6m=8(3m-2)-7m | | 3(4m+5)+6m=5(6y+3)-8 | | 3x+40=320 | | 4x^2-x^2-81=0 | | 10(3a-5)+8=9(4a+3)-5a | | x^2-2x-74=0 | | 4(7y+2)+y=5(6y+3)-8 | | 6(2w+8)+3w=2(10w-5)-4w | | 8(4n+3)-5=7(5n-4)-2n |